Characterization of the properties of composite resins for restorations of deciduous teeth: literature review (Research, Society and Development, 2022)
Due to the large offer of the most diverse options of dental composite resins, there is a doubt about their success when used in pediatric patients, since this group of patients usually requires behavioral management due to their young age and lack of understanding of the facts that are happening around them. Currently, available resins can be classified according to several criteria, such as the amount of inorganic filler, the particle size of the inorganic filler, components of the organic matrix, bonding agent used, among others. The aim of this study was to identify the criteria for selection of the type of composite resin for restorations in deciduous teeth in children with high caries risk, so that it can be consulted serving as an informational base for both academics and dental professionals. After analyzing all the material used as a bibliographic basis for the preparation of this work, it was possible to conclude that currently there is a wide variety of composite resins available in the market that present good results when used in pediatric patients. However, just choosing an adequate composite resin is not enough to obtain excellent results; it is necessary that the operator has the ability and conditions to perform the work with behavioral management techniques. Further studies on the proposed theme are recommended in order to obtain robust scientific evidence that can guide the choices of clinicians and pediatric dentists when selecting composite resins and other restorative materials for children's dental clinics.